Transcriptional Regulation of Macrophages Polarization by MicroRNAs - Li, Heng; Jiang, Ting; Li, Meng-Qi; Zheng, Xi-Long; Zhao, Guo-Jun (Frontiers in Immunology, 2018)
Diversity and plasticity are the hallmarks of cells from the monocyte–macrophage lineage. Macrophages undergo classical M1 or alternative M2 activation in response to the microenvironment signals. Several transcription factors, such as PPARs, STATs, C/EBPs, IRFs, KLFs, GATA3, NF-κB and c-MYC, were found to promote the expression of specific genes, which dictate the functional polarization of macrophages. Importantly, these transcription factors can be regulated by microRNAs (miRNAs), a group of small noncoding RNAs, which regulate gene expression through translation repression or mRNA degradation. Recent studies have also revealed that miRNAs control macrophage polarization by regulating transcription factors in response to the microenvironment signals. This review will summarize recent progress of miRNAs in the transcriptional regulation of macrophage polarization, and provide the insights into the development of macrophage-centered diagnostic and therapeutic strategies.